2016
DOI: 10.1155/2016/7193075
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Biopsy on Human Embryo Developmental Potential during Preimplantation Genetic Diagnosis

Abstract: Preimplantation Genetic Diagnosis and Screening (PGD/PGS) for monogenic diseases and/or numerical/structural chromosomal abnormalities is a tool for embryo testing aimed at identifying nonaffected and/or euploid embryos in a cohort produced during an IVF cycle. A critical aspect of this technology is the potential detrimental effect that the biopsy itself can have upon the embryo. Different embryo biopsy strategies have been proposed. Cleavage stage blastomere biopsy still represents the most commonly used met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
131
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(136 citation statements)
references
References 81 publications
2
131
0
3
Order By: Relevance
“…It may demonstrate the embryos' difficulty to overcome the interference of a blastomere biopsy. An interesting explanation may be that embryos at this stage of preimplantation development are relatively fragile since embryonic genome activation and cell differentiation processes have not yet occurred [8]. Thus, downstream developmental processes can be irreparably compromised by removing a cell from the embryo.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It may demonstrate the embryos' difficulty to overcome the interference of a blastomere biopsy. An interesting explanation may be that embryos at this stage of preimplantation development are relatively fragile since embryonic genome activation and cell differentiation processes have not yet occurred [8]. Thus, downstream developmental processes can be irreparably compromised by removing a cell from the embryo.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently suggested that a trophectoderm biopsy from a day 5 blastocyst has a less harmful effect on further embryonic development compared to blastomere biopsy of day 3 cleavage-stage embryos [3,8,11,44,45]. Scott et al identified blastocyst-stage biopsy as a procedure that does not affect embryo viability and implantation potential as opposed to blastomere biopsy [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations